Adds to the naturalized and adventive catalogue plants of La Pampa, Argentine (Semiárida, 2020)
In this contribution 23 species of naturalized and adventive plants, are cited for first time tor La Pampa. The synonymy, a short description, the distribution, and the dispersal forms are given. The iconography and a boucher are included. A Iist of 13 species who were cited for J. Williamson (1967) with the iconography and a voucher, is attached.
Keywords: Naturalized and adaptative plants; La Pampa; Argentina